Bax inhibitor‐1 protects from nonalcoholic steatohepatitis by limiting inositol‐requiring enzyme 1 alpha signaling in mice. Issue 2 (18th May 2018) - Lebeaupin, Cynthia; Vallée, Déborah; Rousseau, Déborah; Patouraux, Stéphanie; Bonnafous, Stéphanie; Adam, Gilbert; Luciano, Frederic; Luci, Carmelo; Anty, Rodolphe; Iannelli, Antonio; Marchetti, Sandrine; Kroemer, Guido; et al.
Abstract : Endoplasmic reticulum (ER) stress is activated in nonalcoholic fatty liver disease (NAFLD), raising the possibility that ER stress‐dependent metabolic dysfunction, inflammation, and cell death underlie the transition from steatosis to steatohepatitis (nonalcoholic steatohepatitis; NASH). B‐cell lymphoma 2 (BCL2)‐associated X protein (Bax) inhibitor‐1 (BI‐1), a negative regulator of the ER stress sensor, inositol‐requiring enzyme 1 alpha (IRE1α), has yet to be explored in NAFLD as a hepatoprotective agent. We hypothesized that the genetic ablation of BI‐1 would render the liver vulnerable to NASH because of unrestrained IRE1α signaling. ER stress was induced in wild‐type and BI‐1 –/– mice acutely by tunicamycin (TM) injection (1 mg/kg) or chronically by high‐fat diet (HFD) feeding to determine NAFLD phenotype. Livers of TM‐treated BI‐1 –/– mice showed IRE1α‐dependent NOD‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome activation, hepatocyte death, fibrosis, and dysregulated lipid homeostasis that led to liver failure within a week. The analysis of human NAFLD liver biopsies revealed BI‐1 down‐regulation parallel to the up‐regulation of IRE1α endoribonuclease (RNase) signaling. In HFD‐fed BI‐1 –/– mice that presented NASH and type 2 diabetes, exaggerated hepatic IRE1α, X‐box binding protein 1 (XBP1), and C/EBP homologous protein (CHOP) expression was linked to activated NLRP3 inflammasome and caspase‐1/‐11. Rises in interleukin (IL)‐1β, IL‐6, monocyte chemoattractant protein 1 (MCP1), chemokine (C‐X‐C motif) ligand 1 (CXCL1), and alanine transaminase (ALT)/aspartate transaminase (AST) levels revealed significant inflammation and injury, respectively. Pharmacological inhibition of IRE1α RNase activity with the small molecules, STF‐083010 or 4μ8c, was evaluated in HFD‐induced NAFLD. In BI‐1 –/– mice, either treatment effectively counteracted IRE1α RNase activity, improving glucose tolerance and rescuing from NASH. The hepatocyte‐specific role of IRE1α RNase activity in mediating NLRP3 inflammasome activation and cell death was confirmed in primary mouse hepatocytes by IRE1α axis knockdown or its inhibition with STF‐083010 or 4μ8c. Conclusion: Targeting IRE1α‐dependent NLRP3 inflammasome signaling with pharmacological agents or by BI‐1 may represent a tangible therapeutic strategy for NASH. (Hepatology 2018).